Pengawasan Dalam Lembaga Pendidikan Islam Di Indonesia - Mufid, Akhmad Musyafa; Zamroni, Zamroni; Nasrowi, Bagas Mukti (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2024)
PAI teachers now also determine the direction and quality of Islamic religious education in schools in the digital era. This article aims to provide information and inspiration for PAI teachers in general and in particular about how to adapt to changing times, especially in the digital era. They are interested in learning how they can continue to contribute and hone their skills. Performance research is a type of quantitative research that collects information through documentation, interviews and observations. The findings of this research indicate that Islamic religious education teachers are in a position to strategically influence the success of Islamic religious education as well as in planning, implementing and evaluating teaching.